Microvascular skin coverage in wounds that expose the Achilles tendon - Barrera-Mera, Baltazar; Salgado-Adame, Israel; Grajeda-Chávez, Obed Horacio; Chávez-Hernández, Jazmín Danaé; Aguilar-Barragán, Cuauhtémoc; Abundez-Pliego, Ana Lilia; Jiménez-Caprielova, Yuri; Hernández-Arteaga, Leonel Dalain; de la Rosa Llergo, Román Alberto; Pérez-López, José Enrique; Valderrama-Treviño, Alan Isaac (International Journal of Research in Medical Sciences, 2021)
Achilles tendon rupture is one of the most frequent tendon ruptures. Surgical intervention is the best option, but it has a high rate of complications leading to skin infections and necrosis. Extensive and aggressive debridement is necessary, producing tendon exposure and large skin defects. There are many alternatives for the skin coverage of the Achilles tendon, like sequential closures, vacuum assisted closure, local flaps, regional flaps, and more recently and efficiently microsurgery flaps. Skin defects in the Achilles tendon region have many peculiarities in comparison with other parts of the body: it is a zone that is always under mechanical stress due to footwear, this is why it must be highly resistant but thin. Its coverage must have sensitive properties, endure tendon gliding and allow early rehabilitation. Sometimes tendon reinforcement or creation or a neo tendon will be needed. For fulfilling these requirements free flaps by microsurgery are the only option in 90% of the cases. In this review article, we analyze three of the most frequently used free flaps in reconstructive medicine for complex Achilles tendon defects; free radial forearm flap, free radial forearm flap with vascularized flexor carpi radialis tendon and free anterolateral thigh (ALT) flap with vascularized fascia lata. This choice will be determined by the number of tissues involved, size of the defect, etiology of the defect, overall condition of the affected extremity and quality of neighboring tissues.